A Sociolinguistic Analysis of Selected Historical and Non-Historical Proverbs in Yorùbá - Oladeji, Kehinde Olasunkanmi; Adeoye, Jelili Adewale (NIU Journal of Humanities, 2026)
Existing works on Yorùbá historical proverbs submits that such proverbs are a veritable source of history which emphasises various moral and ethical values while studies on non- historical proverbs dwell on their different uses and functions ranging from role relationship in the society, morality, decency, caution and peaceful co-existence. None of the existing works has addressed a comparative analysis of historical and non-historical proverbs, the language choices and their sociolinguistic implications. This study investigates a socioliguistic view of historical and non-historical proverbs. It analyses the genealogy of the Yorùbá proverbs from the historical and non-historical perspectives, explores the use of the proverbs in everyday discourse and how they shape the attitudes, perception and worldview of the Yorùbá people. Emphasis is placed on the social, cultural, and the linguistic contexts of the proverbs. The study also examines how the proverbs are used to articulate collective values and beliefs, and how their meanings are modified and transferred over time. This study adopts Dell Hymes (1972) ethnography of communication for its analysis. The data for this study were obtained from native speakers of Yorùbá in their towns and villages such as Òsogbo, Ọ̀yọ́, Ìbàdàn, Ìkirè, Ògbómọ̀ṣọ̣́, Ọ̀fà and Ìjàbẹ́. Proverb texts were also used for clarification on meaning and explanations. This study is partly a reaction to Lucas (1965) claim that proverbs are anonymous wisdom. Findings in this study show that historical proverbs are product of historians who witnessed the events that are used as references before they became proverbs. The study also argues that non-historical proverbs are products of creativity and deep thought. This study calls for a dichotomy in the acknowledgments rendered before relating the two proverbs (historical and non-historical), such that tributes given to the historians who witnessed the history and those to whom they handed them over to should differ from the creative thinkers who through their ingenuity, invented proverbs. This study contributes to knowledge by recommending different pre-proverbs acknowledgments rendition before the historical and non-historical proverbs to show their sources. Keywords: Historical Proverbs, Non-Historical Proverbs, Sociolinguistics, Historians, Creative Thinkers, Yorùbá Language.